Measles outbreak investigation in a highly vaccinated community in the Centre region of Cameroon - Eposi C. Haddison; Randolph A. Ngwafor; Benjamin M. Kagina (AOSIS, 2021)
Background: Measles remains a threat in many African settings due to sub-optimal routine immunisation and catchup campaigns. The Global Vaccine Action Plan goal to eliminate measles by 2020 remains unmet as several countries reported an increase in cases in 2019. In Cameroon, a measles-rubella vaccination campaign was organised in 2019 to reduce the cohort of susceptible children. However, in 2020, eleven suspected cases of measles were notified in the Sa'a Health District and five were confirmed. Objective: This report summarizes a measles outbreak investigation and contact tracing in a highly vaccinated community residing in the Sa'a Health District of Cameroon. Methods: Outbreak investigations were carried out in the Sa'a, Nlong-Onambele and Nkolmgbana health areas from 18 to 21 February 2020. A register review from December 2019 to February 2020 was carried out in all health facilities of the affected health areas. followed by contact tracing in the community. Results: Thirty households were visited in four neighbourhoods. Six missed Epidemiologically-linked cases were discovered in the community, bringing the total number of suspected and confirmed cases to 17. Thirty-five percent of the cases had not received any measles-containing vaccine; 35% of the cases were aged 5 years or older; 53% had history of travel. Community transmission only occurred in the Sa'a health area through a breakthrough case. Conclusions: This outbreak investigation portrayed the role that adequate vaccination coverage plays in preventing widespread outbreaks. Nonetheless, community sensitisation and routine immunisation require strengthening in order to erase pockets of susceptible children.